Funders’ responsibility to ensure value in research: a self-audit by the Health Research Board Ireland - Cody, Anne (HRB Open Res, 2021)
As a public funder of health research, the Health Research Board (HRB) Ireland has an obligation to manage its funds well and to maximise the value of the research that it funds. Ways in which research funding can be wasted have been examined by researchers over the years, and a seminal series on research waste was published in the Lancet in 2014. The series systematically analysed every step of the funding lifecycle in five major stages and made recommendations to various actors including research funders. Prompted by its participation in the Ensuring Value in Research Funders’ Forum, between June and October 2019 the HRB undertook a self-audit against the 17 recommendations identified in the Lancet series. Key HRB staff collated relevant policies and practices regarding each recommendation and sub-recommendation and assessed the HRB’s performance under each heading. The self-assessment reflects the state of HRB policies and practices in October 2019.  Of the 17 recommendations, five were found to be areas of strength and six were found to be areas of partial strength. Areas of strength reflect work over many years such as support for evidence synthesis, strong processes around award selection, driving research integrity and open data including an HRB-funded open publishing platform. Four recommendations were found to be areas for growth. These mostly revolve around real time reporting of study protocols and of ongoing funded research outside of clinical trials. Work is progressing to address some of these areas. Two were found not to apply to the HRB.